2011
DOI: 10.1016/j.trb.2011.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Distribution-free travel time reliability assessment with probability inequalities

Abstract: An assumption that pervades the current transportation system reliability assessment literature is that probability distributions of the sources of uncertainty are known explicitly. However, this distribution may be unavailable (inaccurate) in reality as we may have no (insufficient) data to calibrate the distribution. In this paper we relax this assumption and present a new method to assess travel time reliability that is distribution-free in the sense that the methodology only requires that the first N momen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…In the future, the proposed framework can be extended to consider uncertainties (Ng, Szeto, and Waller 2011;Szeto, Jiang, and Sumalee 2011a;Szeto, Solayappan, and Jiang 2011b), other types of dynamics (e.g. Szeto 2002, 2005;Watling and Cantarella 2013;Szeto 2013;Wong et al 2014), and transit network design decisions (Szeto and Wu 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the future, the proposed framework can be extended to consider uncertainties (Ng, Szeto, and Waller 2011;Szeto, Jiang, and Sumalee 2011a;Szeto, Solayappan, and Jiang 2011b), other types of dynamics (e.g. Szeto 2002, 2005;Watling and Cantarella 2013;Szeto 2013;Wong et al 2014), and transit network design decisions (Szeto and Wu 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It should be also mentioned that this assumption has also been frequently used in the literature [33], [34]. In fact, Park [35] investigated the correlation between neighboring links and showed that the correlation between neighboring links generally decreases over time.…”
Section: Appendix Independence and Normality Assumptionsmentioning
confidence: 95%
“…These studies focused on the driver's risk-taking behaviour. Ng et al (2011) proposed a methodology to assess travel time reliability under unknown travel time distribution. The method proposed in their study is useful when we do not have enough data to calibrate the travel time distribution.…”
Section: Introductionmentioning
confidence: 99%